'La Nouvelle Vague, elle t'emm---!' Louis Malle, Zazie dans le métro and the French New Wave. (2nd October 2019) - Morrey, Douglas
ABSTRACT: Zazie dans le métro (1960) appears as a quintessentially New Wave film with its youthful protagonist, its location shooting and its many references to cultural history. In addition, the self-conscious play with film technique in Zazie can be seen as a way of exploring the formal specificities of cinema. The film's deployment of popular genre equates to Raymond Queneau's use of demotic register and director Louis Malle takes a ludic approach to film grammar (as Queneau does to French grammar) in order to confuse or elide space and time. Yet the film did not meet with the success of other New Wave films and has not been canonized in the same way. This article suggests one explanation may be the comparative lack of indexical connection to a society in a period of acute social change. Indeed, the film challenges the very concept of indexicality through its proliferation of copies and eerie visual jokes about sameness. Zazie dans le métro is a self-contained circuit that seems, at times, almost to mock the New Wave itself.